The combination of allicin with domiphen is effective against microbial biofilm formation - Li, Shang; Wang, Yutong; Xu, Geweirong; Xu, Yuqing; Fu, Cuiyan; Zhao, Quanlin; Xu, Linjie; Jia, Xinzhou; Zhang, Yumeng; Liu, Yi; Qiao, Jiaju (Frontiers in Microbiology, 2024)
Microorganisms in biofilms are particularly difficult to control because of their increased survival and antibiotic resistance. Allicin and domiphen were employed to inhibit the microbial growth and biofilm formation of Staphylococcus aureus, Escherichia coli, and Candida albicans strains. The two drugs showed synergistic effects against the pathogens with a fractional bactericidal concentration of less than 0.38. The combination of 64 μg/mL allicin with 1 μg/mL domiphen dispersed over 50% of the biofilm mass of S. aureus, E. coli, and C. albicans. In addition, the drug combination reduced the total viable counts of E. coli and C. albicans biofilm cells on stainless steel and polyethylene surfaces by more than 10 2 CFU/mL. Thus, the combination of allicin and domiphen is an effective strategy for efficiently decreasing biofilms formation on various industrial materials surfaces.